Performance of purslane biomass production (Portulaca oleracea) under different organic substrate concentrations - Elias de Oliveira, J.; Barboza Pereira, J.; da Silva, Ch. G.; das Graças Teixeira, A.; Pin Dalvi, L.; de Oliveira, F. L. (Peruvian Agricultural Research, 2020)
Objectives: To evaluate different concentrations based on cattle manure as an alternative in purslane production. Methodology: The experiment was conducted in a greenhouse at the Center for Agricultural Sciences and Engineering of the Federal University of Espirito Santo in Alegre, ES/ Brazil. The experimental arrangement used was a completely randomized design (CRD) with 5 treatments and 6 replications. The treatments consisted of distinct dosages of the substrate based on cattle manure (0 mL; 125 mL; 250 mL; 500 mL and 1000 mL), which were applied in 5 L of soil, considered as an experimental unit. Root dry mass and aerial dry mass were evaluated. Results: Application of 500 mL of cattle manure provided a higher accumulation of shoot dry mass (25 g/plant). For root dry mass, there were no statistically significant differences. Conclusions: Under the conditions of the present work, it is concluded that the use of organic manure with cattle manure is viable. Keywords: Organic fertilization, fertilization levels, cattle manure; dry weight.